High-Performance Perovskite Quantum Dot Solar Cells Enabled by Incorporation with Dimensionally Engineered Organic Semiconductor - Lim, Seyeong; Lee, Dae Hwan; Choi, Hyuntae; Choi, Yelim; Lee, Dong Geon; Cho, Sung Beom; Ko, Seonkyung; Choi, Jongmin; Kim, Younghoon; Park, Taiho (Nano-Micro Letters, 2022)
Perovskite quantum dots (PQDs) have been considered promising and effective photovoltaic absorber due to their superior optoelectronic properties and inherent material merits combining perovskites and QDs. However, they exhibit low moisture stability at room humidity (20–30%) owing to many surface defect sites generated by inefficient ligand exchange process. These surface traps must be re-passivated to improve both charge transport ability and moisture stability. To address this issue, PQD-organic semiconductor hybrid solar cells with suitable electrical properties and functional groups might dramatically improve the charge extraction and defect passivation. Conventional organic semiconductors are typically low-dimensional (1D and 2D) and prone to excessive self-aggregation, which limits chemical interaction with PQDs. In this work, we designed a new 3D star-shaped semiconducting material (Star-TrCN) to enhance the compatibility with PQDs. The robust bonding with Star-TrCN and PQDs is demonstrated by theoretical modeling and experimental validation. The Star-TrCN-PQD hybrid films show improved cubic-phase stability of CsPbI3-PQDs via reduced surface trap states and suppressed moisture penetration. As a result, the resultant devices not only achieve remarkable device stability over 1000 h at 20–30% relative humidity, but also boost power conversion efficiency up to 16.0% via forming a cascade energy band structure.[Figure not available: see fulltext.]
Keywords: Cell stability; CsPbI3 quantum dot; High-efficiency photovoltaic; Higher efficiency; Hybrid perovskite quantum dot; Moisture stability; Performance; Photovoltaics; Solar cell stability; Star-shaped organic semiconductors; CsPbI3 quantum dots; High-efficiency photovoltaics; Hybrid perovskite quantum dots; Solar cell stability; Star-shaped organic semiconductors